Correlation of hearing impairment and communication disorder among geriatric in geriatric clinic, dr. Soetomo hospital surabaya - M, A Ratna Kartika; Purnami, Nyilo; Liben, Paulus (Folia Medica Indonesiana, 2016)
The objective of this study was to analyze correlation between hearing impairment and communication disorder among geriatrics in Geriatric Clinic, Dr. Soetomo Hospital. A randomized cross-sectional study design has been used in this study. Analysis was done by filling in some questionnaire and interview to some patients who were randomly selected according to predetermined condition. The data were collected and reviewed for the factors, which were assumed as risk factors of hearing disorder and life's quality deterioration. Statistical analysis was performed using Fisher's Exact Test using SPSS program version 17. Results showed correlation between hearing impairment and the quality of life and social communication (p=0.033, OR=6.11). However, there was no correlation between hearing impairment with diabetes mellitus (p=0.255), with hypertension (p=0.565), and noisy environment (p=0.689). In conclusion, the study showed that there is correlation between hearing impairment and communication disorder.